The role of eutherian‐specific RTL1 in the nervous system and its implications for the Kagami‐Ogata and Temple syndromes. (16th February 2021) - Kitazawa, Moe; Sutani, Akito; Kaneko‐Ishino, Tomoko; Ishino, Fumitoshi
Abstract: RTL1 (also termed paternal expressed 11 ( PEG11 )) is considered the major imprinted gene responsible for the placental and fetal/neonatal muscle defects that occur in the Kagami–Ogata and Temple syndromes (KOS14 and TS14, respectively). However, it remains elusive whether RTL1 is also involved in their neurological symptoms, such as behavioral and developmental delay/intellectual disability, feeding difficulties, motor delay, and delayed speech. Here, we demonstrate that the mouse RTL1 protein is widely expressed in the central nervous system (CNS), including the limbic system. Importantly, two disease model mice with over‐ and under‐expression of Rtl1 exhibited reduced locomotor activity, increased anxiety, and impaired amygdala‐dependent cued fear, demonstrating that Rtl1 also plays an important role in the CNS. These results indicate that the KOS14 and TS14 are neuromuscular as well as neuropsychiatric diseases caused by irregular CNS RTL1 expression, presumably leading to impaired innervation of motor neurons to skeletal muscles as well as malfunction of the hippocampus‐amygdala complex. It is of considerable interest that eutherian‐specific RTL1 is expressed in mammalian‐ and eutherian‐specific brain structures, that is, the corticospinal tract and corpus callosum, respectively, suggesting that RTL1 might have contributed to the acquisition of both these structures themselves and fine motor skill in eutherian brain evolution. Abstract : RTL1 was detected in most of the corpus callosum, comprising the neurons from cortex layers V and VI, in the neonatal brain. The corpus callosum is unique to eutherians; therefore, Rtl1 may play a role in the emergence of this structure as a eutherian‐specific gene.